Management of Hereditary Angioedema Type 1 and 2 for Canadian Allergy and Immunology Practitioners (Actualité en allergologie et en immunologie au Canada, 2023)
It is imperative for allergists and immunologists to accurately confirm the diagnosis of HAE and coordinate individualized, patient-centred treatment. The 2019 International/Canadian Hereditary Angioedema Guideline, provides an evidence-based approach to managing HAE patients. The objective of this article is to further assist healthcare providers in caring for patients with a confirmed diagnosis of HAE by outlining an approach to patient counselling and reviewing the principles of therapy. We propose 5 essential items to consider in the management of all HAE patients: 1) Patient education; 2) On-demand therapy; 3) Short-term prophylaxis (STP); 4) Long-term prophylaxis (LTP); and 5) Genetic testing. We will also discuss special considerations for pregnant patients.